OPTIMIZING INFRASTRUCTURE AND DIGITAL TECHNOLOGY TO IMPROVE ACADEMIC SERVICES: THE ROLE OF SCHOOL PRINCIPAL LEADERSHIP - Putri Kinanthi Santika; Mohammad Syahidul Haq; Nuphanudin Nuphanudin; Amrozi Khamidi (Academic Journal Research, 2026)
Objective: This study aims to analyze how educational facilities, digital technology, and principal leadership are integrated to enhance academic services in public elementary schools. Method: A qualitative multisite case study design was employed in two public elementary schools in East Java, Indonesia. Data were collected through interviews, observations, and documentation involving principals, teachers, administrative staff, and school committee members. Data were analyzed through within-site analysis using open, axial, and selective coding, followed by cross-site analysis using the constant comparative method. Results: The findings reveal that the effectiveness of academic services is determined not merely by the availability of facilities but by schools’ ability to optimize and integrate educational resources with digital technology through strategic leadership. Schools with different levels of facility availability were able to provide effective academic services through resource optimization strategies, digital transformation, and adaptive instructional leadership. Novelty: Theoretically, this study extends the application of the Resource-Based View in educational management by integrating digital leadership and facilities management. Practically, the findings provide a basis for developing more effective and sustainable educational facility management policies to improve academic service quality.